Trade policies to promote the circular economy: A case study of the plastics value chain - Moïsé, Evdokia (OECD Trade Policy Papers, 2023)
Plastic products present several environmental, health, social and economic challenges that span from the extraction of raw materials to primary and final plastics production, to their distribution and use, and to the collection and sorting of plastic waste. International trade, which has facilitated the development of plastics supply chains, also comes with a range of challenges, such as a surge in demand for plastics - notably in packaging - difficulties to monitor plastics embedded in other products, and an increased risk of plastic waste leaking in countries that have less rigorous environmental regulations. Yet trade can also serve as a vehicle to access foreign pollution control technologies or to foster economies of scale for circular economy practices. Indeed, the implementation of circular economy solutions through trade policies is crucial in addressing plastic pollution. Such policies could include reduced tariffs on environmentally-friendly alternatives to plastic products; trade facilitation measures for reverse supply chains; or technical regulations, standards, labelling schemes, and conformity assessment procedures that promote product designs which will minimise pollution throughout the entire plastic lifecycle